Muscle Hypertrophy Responses to Changes in Training Volume: A Retrospective Analysis - de Camargo, Júlio Benvenutti Bueno; Barbosa, Paulo Henrique; Brigatto, Felipe Alves; Braz, Tiago Volpi; Lopes, Charles Ricardo (International Journal of Sports Medicine, 2023)
This study assessed associations between changes in the weekly number of sets performed and the percentage change in muscle thickness of the biceps (MTBB) and triceps (MTTB) brachii muscles. Through a retrospective analysis, sixty-eight resistance-trained subjects that participated in previous studies had their previous training volumes analyzed and compared to the volume imposed during each individual study. The relationship between variables was determined through Spearman correlation and a k-cluster analysis was performed to subdivide the participants into three groups and classified as:<0%; 0–50%, and >50% increase in the number of sets for both muscle groups. Moderate and weak correlations were observed between the alterations in training volume and changes in MTBB (rs=0.44, p=0.001) and MTTB (rs=0.35, p=0.002), respectively. A significant difference was noted between<0% to >50% for MTBB and MTTB (p=0.017; p=0.042, respectively), while no significant difference was observed between<0% to 0–50% and 0–50% to >50% (both p >0.05) for both muscle groups. In conclusion, muscle hypertrophy of the upper limbs is only weakly to moderately associated with changes in training volume of trained subjects.
Keywords: strength training; number of sets; morphology; muscle thickness